Improving color stability of beef top round - L.M. Sammel; Melvin C. Hunt; Donald H. Kropf (Kansas Agricultural Experiment Station Research Reports, 2001)
The beef inside round muscle, especially the deep portion, has poor color stability, a troublesome condition for the meat industry. We examined influences of pre-rigor temperature and pH decline on chemistry of the inside (deep) semimembranosus (ISM) and outside (surface) semimembranosus (OSM) in relation to initial color and stability. Cold-boned ISM had a slower chill rate; faster pH decline; more denatured protein; less metmyoglobin reducing ability, oxygen consumption, and water holding capacity; and a lighter, less stable color than the OSM. Cold-boned steaks were two-toned in color and discolored by day 3 of display. Hotboned ISM and OSM chilled at the same rate, had similar pH declines, similar chemical characteristics, and acceptable color traits up to day 5 of display. Techniques that chill the entire beef SM faster produced a more uniform stable color, extended the color life of the ISM, and minimized rework and discounting.
Keywords: Cattlemen' s Day; 2001; Kansas Agricultural Experiment Station contribution; no. 01-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 873; Beef; Semimembranosus; Color stability; Metmyoglobin; Reducing activity